The publication rate of abstracts presented at the 2003 urological brazilian meeting - Leonardo Resende Sousa Oliveira; André Avarese Figueiredo; Mauro Choi; Carlos Eduardo Prata Fernandes Ferrarez; Andre Netto Bastos; Jose Murillo Bastos Netto (Clinics, 2009)
OBJECTIVE: To determine the publication rate of orally-presented abstracts from the 2003 Urological Brazilian Meeting, as well as the factors determining this publication rate. MATERIALS AND METHODS: The publication rate of the 313 orally-presented abstracts at the 2003 Urological Brazilian Meeting was evaluated by scanning the Lilacs, Scielo and Medline databases. The time between presentation and publication, the state and country of the abstract, the research methodology (cross-sectional, case-control, retrospective case series, prospective case series or clinical trial), whether drugs were utilized and the topic of the study were all characterized. RESULTS: Thirty-nine percent of the abstracts were published after a median time of 14 months (range: 1 to 51 months). There were high publication rates for cross-sectional abstracts (75%), drug utilization studies (51.3%), clinical trials (50%) and prospective case series' (48.1%). However, there was only a moderate statistical trend towards a higher publication rate in the prospective case series (p=0.07), while the retrospective case series' showed statistically lower publication rates than the other groups (33.7%, p=0.04). Abstracts on laparoscopic surgery had the highest publication rate (61.9%, p=0.03) compared to others topics. In 57% of the unpublished abstracts, there was no interest in or attempt to publish, and rejection was responsible for the lack of publication of only 4% of the abstracts. CONCLUSION: The publication rate of the orally-presented abstracts from the 2003 Urological Brazilian Meeting was comparable to that of international congresses. The subsequent publication of presented abstracts and the selection of prospective studies with stronger evidence should be encouraged and may improve the scientific quality of the meeting.